2001
DOI: 10.1111/j.1553-2712.2001.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Supervision in the Emergency Department: A Costly Inefficiency for Academic Medical Centers

Abstract: Law XI: Show me a BMS (best medical student) who only triples my work and I will kiss his feet. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Many EM faculty members feel torn between their clinical and education duties believing that there is a trade off between efficient patient care and high quality bedside teaching 1. Supervision and teaching of novice practitioners takes time and nowhere in the hospital is the challenge of balancing the ‘joint product lines’ of clinical care and bedside teaching felt more acutely than in the emergency department (ED) 2. Emergency doctors are forced to allocate their most vital resource—their time—carefully, and different doctors choose to allocate this resource in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Many EM faculty members feel torn between their clinical and education duties believing that there is a trade off between efficient patient care and high quality bedside teaching 1. Supervision and teaching of novice practitioners takes time and nowhere in the hospital is the challenge of balancing the ‘joint product lines’ of clinical care and bedside teaching felt more acutely than in the emergency department (ED) 2. Emergency doctors are forced to allocate their most vital resource—their time—carefully, and different doctors choose to allocate this resource in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Others have previously reported that staff physicians are able to make shorter dispositions of patients than residents. 12 We were unable to demonstrate this.…”
Section: Discussionmentioning
confidence: 74%
“…One claim is that the presence of residents increases faculty staffing requirements, as attending physicians are required to spend time supervising and instructing the residents (DeBehnke, 2001). On the other hand, Knickman et al (1992) argue that teaching and treatment can occur simultaneously, meaning that residents can help to improve throughput.…”
Section: Literature Reviewmentioning
confidence: 99%